Analisis Kelengkapan Pengisian Berkas Rekam Medis dan Ketepatan Pengembalian Berkas Rekam Medis Pasien Rawat Inap di Rumah Sakit Universitas Airlangga - Prananingtias, Rosita; Peristiowati, Yuly; Suprapto, Sentot Imam (Universitas Faletehan, 2023)
The implementation of medical records in hospitals can support the improvement of service quality through a fast and accurate documentation, so that the information produced is more effective and efficient. At Airlangga University Hospital, one of indicators of service that hadn’t been achieved was incompleteness of filling and returning medical record that exceeded 2x24 hours after service. The aim of the study was to analyze the implementation of filling and returning medical record for inpatients at Airlangga University Hospital. The research design was qualitative, using in-depth interview techniques with 30 main informants from doctors and nurses and 5 triangulation informants from assembling monitoring and medical record distribution officers. The results of the study illustrated that the implementation of filling and returning medical record was still lacking. In the input component, the doctor's activity and the number of items in the medical record caused incomplete filling. There was no reward and punishment policy from the hospital. In the process component, the incomplete medical records were found and the return of medical record wasn’t timely. In the output component, the most unfilled medical record forms were 58% informed consent and 33% doctor's signature. It was recommended that the hospital hold workshop about medical records and make policies related to reward and punishment.